Edukasi Berbasis Video tentang Pencegahan Kegawatan Hipertensi - Naylil Mawadda Rohma; Rika Maya Sari; Nurhidayati Nurhidayati (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Hypertension is one of the major health problems that can lead to serious complications if not properly controlled. The lack of public knowledge regarding the signs, risk factors, and prevention of hypertensive emergencies is a challenge in promotive and preventive efforts. Video as an educational medium has advantages because it is audio-visual, engaging, and easy to understand. Objective: This community service activity aimed to improve public knowledge regarding the prevention of hypertensive emergencies through video-based health education. Method: The activity was carried out using a health education approach with video media containing materials on the signs and symptoms of hypertensive emergencies, risk factors, and preventive measures. Evaluation was conducted by measuring knowledge before and after the intervention using a questionnaire. Data were analyzed using statistical tests. Result: The results showed a significant increase in public knowledge after being given video-based education with a value of p = 0.000 (p < 0.05). This proves that video media is effective as a health education tool Conclusion: Video-based health education is proven to be effective in improving public knowledge regarding the prevention of hypertensive emergencies. This media can be used as an alternative sustainable education strategy in promotive and preventive efforts at the community level.